Training Effectiveness In Improving Teachers Professionalism Competence In School - Sukartono, Sukartono; Samsudi, Samsudi; Raharjo, Tri Joko; Sugiharto, DYP. (The Journal of Educational Development, 2016)
A training which is packaged and managed theoretically and practically will produce an effective training concept. Such training will facilitate the achievement of the expected goals. A training which starts from the planning, organizing, coordinating, implementing and evaluation will be carried out effectively if it meets the requirements, namely clear objectives, based on needs, based on the data results of mapping and competency tests, conductedregularly and periodically, budget savings, easy to be implemented and disseminated, and followed by monitoring and evaluation. Training effectiveness related to professional competence of teachers is a training which is able to produce a comprehensible figure of teacher and is able to provide materials for behavioral change to carry out their duties at school. The provided training is not only for refreshment, but also to nurture and develop the potential and competency of teachers when carrying out their tasks. Training is given not merely because of obligatory program or pursuing the budget spending target, but it is actually used to form a professional teacher. Therefore, a training needs to be managed from beginning to end. Training even should involve various stakeholders so that the training can be used as a regular program to improve the quality of teachers.